2015
DOI: 10.5424/fs/2015241-05077
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term effects of weed control and fertilization on growth and wood anatomy of a Populus deltoides clone

Abstract: Aims of study: The short- and long-term effects of weed control and fertilization on growth and wood anatomy of 10-y-old Populus deltoides were investigated. Weed control and fertilization usually leads to an increase the growth rate of trees, and consequently, a possible modification in the quality of produced wood.Area of study: We analyzed trees from an experimental plantation in Buenos Aires, Argentina (34°50’ S Lat; 60°30’ W Long).Methods: 32 trees from three treatments: mechanical weed control (M), chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The short-term effect of nitrogen on the anatomical properties of poplar wood has been confirmed in the literature [ 38 , 40 ] and in this research. The long-term response to growth was detected after intensive and repeated nitrogen fertilisation [ 49 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The short-term effect of nitrogen on the anatomical properties of poplar wood has been confirmed in the literature [ 38 , 40 ] and in this research. The long-term response to growth was detected after intensive and repeated nitrogen fertilisation [ 49 ].…”
Section: Discussionsupporting
confidence: 86%
“…The results of this research indicate that only FL was significantly affected by different nitrogen treatments during both years of fertilisation. Research on the Populus deltoides clone [ 40 ] reported longer, thicker, wider fibres and wider vessels after three years of fertilisation. In this research, the application of nitrogen reduced FL in 2004, while only N1 increased FL in 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To an extent, the challenging conditions in the drylands could also be mitigated by various management techniques, i.e., soil preparation and increased water and nutrient availability ( Querejeta et al., 2001 ). Indeed, practices as preparatory fertilization can provide residual long-term effects on tree growth ( From et al., 2015 ; Monteoliva et al., 2015 ; Smolander et al., 2022 ). As part of the Green Belt Plantation Project, a complex experimental design has been implemented to understand the impact of management (fertilization and irrigation) on the development of two species of interest, Populus sibirica Hort, Ex.…”
Section: Introductionmentioning
confidence: 99%
“…To an extent, the challenging conditions in the drylands could also be mitigated by various management techniques, i.e., soil preparation and increased water and nutrient availability (Querejeta et al, 2001). Indeed, practices as preparatory fertilization can provide residual long-term effects on tree growth (From et al, 2015;Monteoliva et al, 2015;Smolander et al, 2022). As part of the Green Belt Plantation Project, a complex experimental design has been implemented to understand the impact of management (fertilization and irrigation) on the development of two species of interest, Populus sibirica Hort, Ex.…”
Section: Introductionmentioning
confidence: 99%